Dehydration-Induced Anorexia Reduces Astrocyte Density in the Rat Corpus Callosum - Daniel Reyes-Haro; Francisco Emmanuel Labrada-Moncada; Ricardo Miledi; Ataúlfo Martínez-Torres (Neural Plasticity)
Anorexia nervosa is an eating disorder associated with severe weight loss as a consequence of voluntary food intake avoidance. Animal models such as dehydration-induced anorexia (DIA) mimic core features of the disorder, including voluntary reduction in food intake, which compromises the supply of energy to the brain. Glial cells, the major population of nerve cells in the central nervous system, play a crucial role in supplying energy to the neurons. The corpus callosum (CC) is the largest white matter tract in mammals, and more than 99% of the cell somata correspond to glial cells in rodents. Whether glial cell density is altered in anorexia is unknown. Thus, the aim of this study was to estimate glial cell density in the three main regions of the CC (genu, body, and splenium) in a murine model of DIA. The astrocyte density was significantly reduced (~34%) for the DIA group in the body of the CC, whereas in the genu and the splenium no significant changes were observed. DIA and forced food restriction (FFR) also reduced the ratio of astrocytes to glial cells by 57.5% and 22%, respectively, in the body of CC. Thus, we conclude that DIA reduces astrocyte density only in the body of the rat CC.